Quality of life and risk of depression and suicide in teachers (Research, Society and Development, 2022)
This study aims to analyze the quality of life and the risk of depression and suicide in university and elementary school teachers in the city of Arapiraca, Alagoas, Brazil. This is a cross-sectional, quantitative and descriptive study. 219 elementary school teachers and 63 university teachers were interviewed. Elementary school (78 - 35.6%) and university (22 - 34.9%) teachers were at risk for depression. Elementary school teachers at risk for depression had a lower mean quality of life in the environment domain. Among university professors, the physical domain was the most compromised. There was a weak association between depression and quality of life in elementary school teachers (Pearson's R: 0.303, p = 0.002) and moderate in university teachers (Pearson's R: 0.535, p = 0.002). Depression was related to the domain of social relationships (p = 0.013) in university professors. Twelve (5.5%) elementary school teachers and 1 (1.6%) university teacher were at risk for suicide. Prevention actions in mental health aimed at teachers are necessary.